2009
DOI: 10.1002/dvdy.22106
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Wnt pathway activity in the mouse incisor indicate absence of Wnt/β‐catenin signaling in the epithelial stem cells

Abstract: The Wnt pathway is crucial for tooth development as shown by dental defects caused by impaired Wnt signaling in mouse and human. We investigated Wnt signaling in continuously growing mouse incisors focusing on epithelial stem cells. Ten Wnt ligands were expressed both in the dental epithelium and mesenchyme, and were associated mainly with odontoblast and ameloblast differentiation. Wnt/b-catenin activity was detected in mesenchyme in BATgal and TOPgal reporter mice while Axin2, also a reporter of Wnt/b-cateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
116
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(127 citation statements)
references
References 58 publications
(87 reference statements)
8
116
2
1
Order By: Relevance
“…However, there are some discrepancies among developmentally dynamic Sulf mRNA expression, 10E4 immunoreactivity, and TOPGAL reporter expression (23). Indeed, Wnt10a mRNA expression and TOPGAL reporter expression are only localized in the odontoblast layer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are some discrepancies among developmentally dynamic Sulf mRNA expression, 10E4 immunoreactivity, and TOPGAL reporter expression (23). Indeed, Wnt10a mRNA expression and TOPGAL reporter expression are only localized in the odontoblast layer.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse Sulf1 and Sulf2 probes were generated from a 461-bp Sulf1 fragment spanning the region between 124 and 584 in accession number AY101178 and a 459-bp Sulf2 fragment spanning the region between 3056 and 3514 in accession number AY101178. The preparation of Wnt10a, Dspp, and Axin2 RNA probes has been described previously (23,26).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in the late bell stage in which dentin and enamel are formed, Wnt-10a mRNA is expressed in preodontoblasts and odontoblasts and dentin sialophosphoprotein (Dspp) mRNA is expressed by odontoblasts, on the basis of which Wnt-10a has been reported to be involved in odontoblast differentiation and dentin formation by regulating Dspp 10) . It has been reported that Wnt-10a and Axin2 appeared in the incisor tooth germ ameloblasts 11) , Wnt10, Dvl, inactive-type GSK-3β and β-catenin distributed in secretory-stage ameloblast and progenitors of the more tooth germ 12) , and β-catenin/LEF1 activates the appearance of enamelin in ameloblast-like cells 13) , indicating involvement of Figure 1. Immunohistochemical observation of the rat first molar germ on embryonic day 19. a Hematoxylin and eosin (H-E) staining.…”
Section: Introductionmentioning
confidence: 90%